My First Truck board book. - Dorling Kindersley, Inc.; Robinson, Constance, editor (Dorling Kindersley, Inc., USA, 1999)
Introduces young children to different types of trucks and construction vehicles using labelled colour photographs. A first word and picture book of trucks, tractors, diggers, and fire engines to increase a child's vocabulary.
Busy trucks -- Carriers -- Fire trucks -- Fire emergency Vehicles -- Road Builders -- Loaders and Lifters -- Dump truck -- Diggers -- Mighty and Little Trucks -- Farm Machines -- Tractor and Attachments.
Photographic illustrations and labels of various trucks and construction vehicles.
1 - 3 years
Text in English.
Keywords: Trucks, Juvenile literature, Board books, Vocabulary